Reading comprehension and co-teaching practices in middle school English language arts classrooms - Wexler, Jade; Kearns, Devin M.; Lemons, Christopher J.; Mitchell, Marisa; Clancy, Erin; Davidson, Kimberly A.; Sinclair, Anne C.; Wei, Yan (Exceptional Children, 2018)
This study reports practices implemented in over 2,000 minutes by 16 middle school special education and general education co-teaching pairs in English language arts classes. We report the extent to which teachers integrated literacy activities that support reading comprehension, the co-teaching models used, and the frequency with which each teacher led instruction. We also report the types of grouping structures teachers used and the extent to which teachers interacted with students with disabilities. Finally, we report the types of text used. Observations revealed that more than half of time spent on literacy activities involved reading aloud or silently with no co-occurring literacy instruction that supports reading comprehension. Students with disabilities spent a majority of their time in whole-class instruction or working independently with little teacher interaction. Special education teachers spent most of their time supporting whole-class instruction led by the content-area teacher. Implications and directions for future research are provided.
Keywords: dept.rdg; dept.sed; peer-reviewed